The Physics of Diving - Fox, S.
There are many laws of physics which are applicable to the sport of diving. Divers can take advantage of these principles in order to perform the best possible dive. CENTER OF GRAVITY AVERAGE ANGULAR VELOCITY FIRST LAW- "THE PRINCIPLE OF INERTIA" Second Law- "The Principle of Acceleration" THIRD LAW- "THE PRINCIPLE OF EQUAL AND OPPOSITE REATCIONS" ANGULAR MOMENTUM